Engineering Microbial Consortia for High-Performance Cellulosic Hydrolyzates-Fed Microbial Fuel Cells - Li, Feng; An, Xingjuan; Wu, Deguang; Xu, Jing; Chen, Yuanyuan; Li, Wenchao; Cao, Yingxiu; Guo, Xuewu; Lin, Xue; Li, Congfa; Liu, Sixin; Song, Hao (Frontiers in Microbiology, 2019)
Microbial fuel cells (MFCs) are eco-friendly bio-electrochemical reactors that use exoelectrogens as biocatalyst for electricity harvest from organic biomass, which could also be used as biosensors for long-term environmental monitoring. Glucose and xylose, as the primary ingredients from cellulose hydrolyzates, is an appealing substrate for MFC. Nevertheless, neither xylose nor glucose can be utilized as carbon source by well-studied exoelectrogens such as Shewanella oneidensis. In this study, to harvest the electricity by rapidly harnessing xylose and glucose from corn stalk hydrolysate, we herein firstly designed glucose and xylose co-fed engineered Klebsiella pneumoniae-S. oneidensis microbial consortium, in which K. pneumoniae as the fermenter converted glucose and xylose into lactate to fed the exoelectrogens (S. oneidensis). To produce more lactate in K. pneumoniae, we eliminated the ethanol and acetate pathway via deleting pta (phosphotransacetylase gene) and adhE (alcohol dehydrogenase gene) and further constructed a synthesis and delivery system through expressing ldhD (lactate dehydrogenase gene) and lldP (lactate transporter gene). To facilitate extracellular electron transfer (EET) of S. oneidensis, a biosynthetic flavins pathway from Bacillus subtilis was expressed in a highly hydrophobic S. oneidensis CP-S1, which not only improved direct-contacted EET via enhancing S. oneidensis adhesion to the carbon electrode but also accelerated the flavins-mediated EET via increasing flavins synthesis. Furthermore, we optimized the ratio of glucose and xylose concentration to provide a stable carbon source supply in MFCs for higher power density. The glucose and xylose co-fed MFC inoculated with the recombinant consortium generated a maximum power density of 104.7 ± 10.0 mW/m2, which was 7.2-folds higher than that of the wild-type consortium (12.7 ± 8.0 mW/m2). Lastly, we used this synthetic microbial consortium in the corn straw hydrolyzates-fed MFC, obtaining a power density 23.5 ± 6.0 mW/m2. These results demonstrated that engineering microbial consortia could effectively expand the carbon source spectrum for electricity power production in MFCs.